Correlation between vitiligo occurrence and clinical benefit in advanced melanoma patients treated with nivolumab: A multi‐institutional retrospective study. Issue 2 (11th August 2016) - Nakamura, Yasuhiro; Tanaka, Ryota; Asami, Yuri; Teramoto, Yukiko; Imamura, Taichi; Sato, Sayuri; Maruyama, Hiroshi; Fujisawa, Yasuhiro; Matsuya, Taisuke; Fujimoto, Manabu; Yamamoto, Akifumi
Abstract: Vitiligo is occasionally seen in melanoma patients. Although several studies indicate a correlation between vitiligo occurrence and clinical response in melanoma patients receiving immunotherapy, most studies have included heterogeneous patient and treatment settings. The aim of this study is to investigate the correlation between the occurrence of vitiligo and clinical benefit of nivolumab treatment in advanced melanoma patients. We retrospectively reviewed unresectable stage III or IV melanoma patients treated with nivolumab. Of 35 melanoma patients treated with nivolumab, 25.7% (9/35) developed vitiligo during treatment. The time from the start of nivolumab treatment to occurrence of vitiligo ranged 2–9 months (mean, 5.2). Of nine patients who developed vitiligo, two (22.2%) had a complete response to nivolumab and two (22.2%) had a partial response. The objective response rate was significantly higher in patients with vitiligo than in patients without vitiligo (4/9 [44.4%] vs 2/26 [7.7%]; P = 0.027). The mean time to vitiligo occurrence in patients achieving an objective response was significantly less than that in patients who showed no response (3.1 vs 6.8 months, P = 0.004). Vitiligo occurrence was significantly associated with prolonged progression‐free and overall survival (hazard ratio, 0.24 and 0.16; 95% confidence interval, 0.11–0.55 and 0.03–0.79; P = 0.005, and 0.047, respectively). At the 20‐week landmark analysis, however, vitiligo was not associated with a statistically significant overall survival benefit ( P = 0.28). The occurrence of vitiligo during nivolumab treatment may be correlated with favorable clinical outcome.